Variation in the Hearing Threshold in Women during the Menstrual Cycle - Souza, Dayse da Silva; Luckwu, Brunna; Andrade, Wagner Teobaldo Lopes de; Pessoa, Luciane Spinelli de Figueiredo; Nascimento, João Agnaldo do; Rosa, Marine Raquel Diniz da (International Archives of Otorhinolaryngology, 2017)
Introduction The hormonal changes that occur during the menstrual cycle and their relationship with hearing problems have been studied. However, they have not been well explained.Objective The objective of our study is to investigate the variation in hearing thresholds in women during the menstrual cycle.Method We conducted a cohort and longitudinal study. It was composed of 30 volunteers, aged 18–39 years old, of which 20 were women during the phases of the menstrual cycle and 10 were men (control group) who underwent audiometry and impedance exams, to correlate the possible audiological changes in each phase of the menstrual cycle.Results There were significant changes in hearing thresholds observed during the menstrual cycle phases in the group of women who used hormonal contraceptives and the group who did not use such contraceptives. Improved hearing thresholds were observed in the late follicular phase in the group who did not use hormonal contraceptives and the hearing thresholds at high frequencies were better. Throughout the menstrual cycle phases, the mean variation was 3.6 db HL between weeks in the group who used hormonal contraceptives and 4.09 db HL in the group who did not use them.Conclusions The present study found that there may be a relationship between hearing changes and hormonal fluctuations during the menstrual cycle based on changes in the hearing thresholds of women. In addition, this study suggests that estrogen has an otoprotective effect on hearing, since the best hearing thresholds were found when estrogen was at its maximum peak.
Keywords: hearing; menstrual cycle; hormones